Synthesis of Furopyrimidine Derivatives - Megid, Mohamed Abdel; El-Kazak, Azza Mohamed; Seada, Magdy Hamed; Farouk, Osama Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Furopyrimidines have been known for many years and have been thoroughly examined in the recent years. The present review deals with description of the various synthetic routes for Â furopyrimidine derivatives.